Colusión en un duopolio de Bertrand con rendimientos decrecientes y productos diferenciados - Roberto Contreras; Nikolaos Georgantzis; Miguel Ginés (Estudios de Economía, 2008)
– We study cartel stability in a differentiated price-setting duopoly with returns to scale. We show that a cartel may be equally stable in the presence of lower differentiation, provided that the decreasing returns parameter is high. In addition we demonstrate that for a given factor of discount, there are technologies that can have decreasing returns to scale where the cartel always is stable independent of the differentiation degree.
Keywords: C70; D21; D43; 330; collusion; product differentiation; decreasing returns to scale; Kartell; Duopol; Produktdifferenzierung; Skalenertrag; Theorie